Study of direct CP violation in B±→J/ ψK±(π±) decays - Abazov, V; Abbott, B; Abolins, M; Acharya, B; Adams, M; Adams, T; Aguilo, E; Ahn, S; Ahsan, M; Alexeev, G; Alkhazov, G; Alton, A; et al. (2008)
We present a search for direct CP violation in B±→J/ ψK±(π±) decays. The event sample is selected from 2.8fb-1 of pp̄ collisions recorded by D0 experiment in run II of the Fermilab Tevatron Collider. The charge asymmetry ACP(B+→J/ψK+)=+0.0075±0. 0061(stat)±0.0030(syst) is obtained using a sample of approximately 40000 B±→J/ψK± decays. The achieved precision is of the same level as the expected deviation predicted by some extensions of the standard model. We also measured the charge asymmetry ACP(B+→J/ψπ+)=-0. 09±0.08(stat)±0.03(syst). © 2008 The American Physical Society.